Analysis of The Translation Results of The German Language Education Study Program Website Article Using ChatGPT - Siburian, Vera Chentia; Titaley, Audrey Gabriella (Proceeding of International Joint Conference on UNESA, 2025)
The rapid development of internet technology has impacted various fields, including language translation. Translation is a complex process that not only transfers messages from the source language to the target language but also considers contextual structure and meaning to avoid errors. With technological advancements, automatic translation tools such as Google Translate, Bing Translator, and DeepL have simplified the translation process. However, the quality of translations produced by these tools, especially for languages with complex structures like German, is often inaccurate. Recently, ChatGPT, an artificial intelligence model developed by OpenAI, has emerged as an alternative for generating more natural and contextual translations. This study focuses on analyzing the translation accuracy of Indonesian to German texts produced by ChatGPT on the academic website content of the German Language Education Program at Universitas Negeri Surabaya. The aim of this research is to evaluate the quality, fluency, and contextual accuracy of the translations, and to assess how well ChatGPT handles the complex grammatical structures of the German language.